Zhilong Huoxue Tongyu Capsules' Effects on ischemic stroke: An assessment using fecal 16S rRNA gene sequencing and untargeted serum metabolomics - Wang, Raoqiong; Liu, Mengnan; Ren, Guilin; Luo, Gang; Wang, Zhichuan; Ge, Zhengxin; Pu, Qingrong; Ren, Wei; Yang, Sijin (Frontiers in Pharmacology, 2022)
Zhilong Huoxue Tongyu capsule (ZHTC) is an effective traditional Chinese medicine compound for the treatment of ischemic stroke, which is widely used in clinical ischemic stroke patients.However, it is uncertain whether ZHTC affects ischemic stroke through gut microbiota and serum metabolites.In this study, a rat model of middle cerebral artery occlusion (MCAO) was prepared. By evaluating motor nerve function score, cerebral infarct size, brain tissue damage and intestinal barrier damage, it was found that ZHTC improved stroke-related symptoms in MCAO rats. Using 16S rRNA gene sequencing, fecal microbial transplantation (FMT), untargeted metabolomics, and spearman correlation analysis of gut microbiota and serum metabolites, we found that ZHTC can regulate the abundance of p__Firmicutes,p__Bacteroidota,p__Proteobacteria, g_Prevotella, and g_Lactobacillus , and regulated 23 differential metabolites.Spearman correlation analysis found that Arginine was positively correlated with p_Firmicutes, o_Clostridiales, c_Clostridia, and negatively correlated with p_Bacteroidetes,c_Bacteroidia,o_Bacteroidales; L-Lysine was negatively correlated with f_Christensenellaceae;L-methionine was positively correlated with o_Lactobacillales,f_Lactobacillaceae,and g_Lactobacillus.Altogether, this study shows for the first time that ZHTC can ameliorate ischemic stroke by modulating gut microbiota and metabolic disturbances. This lays the foundation for further revealing the causal relationship between ZHTC, gut dysbiosis, plasma metabolite levels and ischemic stroke, and provides a scientific explanation for the ameliorating effect of ZHTC on ischemic stroke.